2018
DOI: 10.1016/j.ridd.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Developmental delay in communication among toddlers and its relationship to caregiving behavior among violence-exposed, posttraumatically stressed mothers

Abstract: Results are consistent with the literature that while maternal IPV-PTSD severity is not associated with child language delays, the quality of maternal interactive behavior is associated both with child language development and with maternal IPV-PTSD severity. Further study is needed to understand if the level of child language development contributes to intergenerational risk or resilience for relational violence and/or victimization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…Less well understood is how the trauma effects change during development. The effects of maltreatment can be seen in childhood but identifying these subtle effects can be challenging until early adolescence when psychiatric disorders, as well as fear pathologies, increasingly emerge, with the amygdala and PFC targeted (Demers et al, 2018; Roos et al, 2018; Torrisi et al, 2018). The protracted development of the brain likely contributes to these developmental transitions (Giedd et al, 1999; Lupien et al, 2009; Raineki et al, 2010a,b; Rincon-Cortes et al, 2015; Teicher et al, 2016; Opendak et al, 2017; Hagler et al, 2018; Heany et al, 2018; Hodel, 2018; Lange et al, 2018; VanTieghem and Tottenham, 2018; Botros et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Less well understood is how the trauma effects change during development. The effects of maltreatment can be seen in childhood but identifying these subtle effects can be challenging until early adolescence when psychiatric disorders, as well as fear pathologies, increasingly emerge, with the amygdala and PFC targeted (Demers et al, 2018; Roos et al, 2018; Torrisi et al, 2018). The protracted development of the brain likely contributes to these developmental transitions (Giedd et al, 1999; Lupien et al, 2009; Raineki et al, 2010a,b; Rincon-Cortes et al, 2015; Teicher et al, 2016; Opendak et al, 2017; Hagler et al, 2018; Heany et al, 2018; Hodel, 2018; Lange et al, 2018; VanTieghem and Tottenham, 2018; Botros et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…131 Overall, less optimal internal working models and severity of maternal mood or PTSD symptoms and alexithymia were associa ted with more negative parenting behaviors, lower reflective function, and negative offspring outcomes. 105,110,112,113,119,122,[126][127][128] Further, in families impacted by intimate partner violence, children had more insecure and less stable attachment styles and male offspring were more likely to exhibit aggressive touch. 120,121,123,125 By contrast, more secure maternal adult attachment style was associated with better child outcomes across multiple studies.…”
Section: Childhood Maltreatment Experiences and Impaired Internal Wor...mentioning
confidence: 99%
“…Relationships with offspring and offspring outcomes. Of the 54 articles pertinent to associations between impaired internal working models and early parent-child relationships and offspring outcomes, 14,59,62,63,71,72,76,77,92,[107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][126][127][128][129][130]134,139,147,156,[165][166][167][168][169][170][171][172][173][174][175][176][177]…”
Section: Perinatal Substance Use and Impaired Internal Working Modelsmentioning
confidence: 99%
“…Studies routinely find that positive parenting is associated with better child language outcomes across the earliest years of child development. 17,18 Other research has demonstrated that children whose parents have experienced interpersonal traumas exhibit less language competence when parent-child interactions are strained, 19 suggesting that parenting behavior may be a link between parental experiences of adversity and subsequent child language competence.…”
Section: Adversity Parenting and Child Language Developmentmentioning
confidence: 99%